IMG-10. Determining brain tumour grade non-invasively using a simplified MRI perfusion protocol: single-bolus, leakage-corrected dynamic susceptibility-contrast MRI. (3rd June 2022) - Withey, Stephanie; MacPherson, Lesley; Oates, Adam; Powell, Stephen; Novak, Jan; Bailey, Simon; Mitra, Dipayan; Arvanitis, Theodoros N; Khan, Omar; Rose, Heather E L; Worthinton, Lara; Peet, Andrew C
Abstract: INTRODUCTION : Perfusion is associated with grade and survival in children's brain tumours. Dynamic susceptibility-contrast (DSC-) MRI measures perfusion non-invasively, estimating relative cerebral blood volume (rCBV). We previously showed significant differences between pre-treatment rCBV in low- and high-grade tumours in a multicentre study. Contrast agent leakage from tumour vessels during acquisition affects rCBV accuracy. A contrast agent pre-bolus can be given but this can be challenging in a clinical environment, introducing variability. Alternatively, a single bolus can be administered with leakage correction applied when processing the data. We investigated pre-treatment rCBV values in a multicentre study without pre-bolus administration. METHODS : Thirty-six patients underwent pre-treatment DSC-MRI scans at 2 centres on 4 different scanners. Protocols were variable. Pixel-by-pixel contrast agent concentration time courses were analysed. Maps of uncorrected (rCBVuncorr ) and leakage-corrected rCBV (rCBVcorr ) were produced. Whole-tumour regions-of-interest were defined and median whole-tumour DSC-MRI parameters calculated. Patients subsequently underwent surgery / biopsy. Tumours were classified and graded. RESULTS : Twelve tumours were classified as low-grade; 24 as high-grade. Median whole-tumour rCBVuncorr was significantly higher in high-grade tumours than in low-grade tumours (1.628 vs -0.167, p<0.001). Median rCBV significantly increased in low-grade tumours following leakage correction (-0.167 to 1.072, p=0.007); there was no significant change for high-grade tumours. Using the median rCBVuncorr of 1.19 to differentiate between low- and high-grade tumours resulted in sensitivity and specificity of 75% and 100%, respectively; median 1.45 for rCBVcorr resulted in sensitivity and specificity of 67% and 100%, respectively. DISCUSSION : DSC-MRI measures of perfusion can distinguish between low- and high-grade paediatric brain tumours. Contrast agent leakage correction is essential for accurate measurement of rCBV. This is robust across multiple centres despite using multiple protocols. CONCLUSION : Pre-treatment multicentre perfusion MRI acquired with a single-bolus and contrast agent leakage correction can aid with differentiating between high- and low-grade paediatric brain tumours.